2009
DOI: 10.1007/s10694-009-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aspect Ratio on Fire Resistance of Hollow Core Concrete Floors

Abstract: Previous studies have shown that the fire performance of hollowcore units is significantly affected by the end support conditions, but it has not been clear how the fire resistance of the overall floor system can be improved by providing side supports. The previous studies used beam grillage and shell elements to separately model the hollowcore units and the topping concrete slab using the platform of the non-linear finite element program SAFIR. The modelling method required a lot of computational resources an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The structural behavior of the hollow core slab under fire was also influenced by axial restraints provided at supports and the fire resistance was enhanced with the provision of axial restraints (Shakya and Kodur, 2015;Thienpont et al, 2023). The load-bearing performance of prestressed hollow-core slab is influenced by various factors such as slab depth (Pothisiri and Kositsornwanee, 2015;Kodur and Shakya, 2017;Heo et al, 2021), length of slab (Chang et al, 2010;Heo et al, 2021), load ratio (Ehab Ellobody, 2014;Kodur and Shakya, 2017;Heo et al, 2021), axial restraints (Shakya and Kodur, 2015;Thienpont et al, 2023), boundary condition (Kodur and Shakya, 2017) and aggregate type (Aguado et al, 2016). Based on an extensive review of the literature, it is observed that factors governing the performance of hollow-core slabs were predicted for standard fire curve exposure and there is limited research considering the worst-case fire scenario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural behavior of the hollow core slab under fire was also influenced by axial restraints provided at supports and the fire resistance was enhanced with the provision of axial restraints (Shakya and Kodur, 2015;Thienpont et al, 2023). The load-bearing performance of prestressed hollow-core slab is influenced by various factors such as slab depth (Pothisiri and Kositsornwanee, 2015;Kodur and Shakya, 2017;Heo et al, 2021), length of slab (Chang et al, 2010;Heo et al, 2021), load ratio (Ehab Ellobody, 2014;Kodur and Shakya, 2017;Heo et al, 2021), axial restraints (Shakya and Kodur, 2015;Thienpont et al, 2023), boundary condition (Kodur and Shakya, 2017) and aggregate type (Aguado et al, 2016). Based on an extensive review of the literature, it is observed that factors governing the performance of hollow-core slabs were predicted for standard fire curve exposure and there is limited research considering the worst-case fire scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The load-bearing performance of prestressed hollow-core slab is influenced by various factors such as slab depth (Pothisiri and Kositsornwanee, 2015; Kodur and Shakya, 2017; Heo et al. , 2021), length of slab (Chang et al. , 2010; Heo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PCHC slabs exposed to fire can fail in bending, anchorage, shear-compression, and web-shear modes (Borgogno and Fontana 2000, Fellinger 2005, Chang, Moss et al 2010, Aguado, Espinos et al 2012, Torić, Divić et al 2012, Jansze, Klein-Holte et al 2014, Shakya and Kodur 2015. Among the four, fire tests conducted over the past 40 years showed that shear and anchorage failures dominate the fire behavior of PCHC slabs rather than bending failure (Fellinger 2004).…”
Section: Failure Modes Of Pchc Slabs Under Fire Conditionsmentioning
confidence: 99%